Odpisano knjižnično gradivo slovenskih knjižnic v obdobju 2005-2010 skozi prizmo nacionalne knjižnice - Poličnik-Čermelj, Tereza (Knjižnica, 2011)
Purpose: In Slovenia, there is no national repository library for the long-term retention of withdrawn library materials. Therefore, the National and university library (NUK) coordinates withdrawals in Slovenian libraries in order to preserve the national cultural heritage. The author highlights collaborative activities of NUK and other libraries to ensure preservation and retention of withdrawn printed materials in terms of professional legislation and guidelines. According to them NUK is authorised to select withdrawn items to be included in the "Slovenica" collection. Methodology/approach: The paper deals with withdrawal statistics of Slovenian libraries during the period 2005-2010. The data were collected by the Library system development centre at NUK in correlation with withdrawal lists sent to NUK by the libraries. Results: The results show that well-preserved but outdated materials are deselected by less than a half of public libraries, by 10% of higher-education libraries, by a little bit more than 5% of special libraries and only by 2% of school libraries. The protocol for data checking, sending the materials to NUK, handling and selection criteria are explained. The advantages and disadvantages of including the withdrawn items into the NUK collection and the disposal of inappropriately selected materials are described. The results of acquiring the last copies of "Slovenica" from the withdrawn materials are more than satisfactory for NUK. Research limitation: As there are no similar models of acquisition among foreign national librarie, the study is limited to Slovenian library practice. Originality/practical implications: The paper also indicates the direction of future development.
Keywords: knjižnično gradivo; purchasing; nabava; odpis; statistični podatki; nacionalne knjižnice; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana